ARTISTIC AMNESIA AND MEMORY IN THE PROSE OF A. P. CHEKHOV: FROM THE IMAGE OF THE DISEASE TO THE SPIRITUAL AND MORAL CONCEPT - Alexander V. Kubasov (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2024)
The article deals with the problem of memory, which arose in the early works of Chekhov, and then evolved over a long period of time. In the story "Forgot!!" the experience of representing the pathological state of memory is implemented. The story was written by a medical student under the influence of university courses in psychiatry. Artistic amnesia is a conditional image of the disease to create a humorous mood. In the story "At Acquaintances", the ability to remember, to live in the past or in the present becomes one of the markers of the characters, a characteristic of their various axiologies. The story "Bishop" is the creative testament of the writer in prose. The problem of memory is interpreted as a space created by the poles of binary oppositions. The end of the life of the title character is associated with the fading of his memory. One of the conclusions of the story can be formulated as follows: life is something that can be remembered.